Neuroprotective Properties of Lactobacillus plantarum: Bridging Gut Health and Cognition - Deepali Deepali; Pavan Kumar Chikkavalli Muddanna; Dhanush Hulikere Koppalu Devaraju; Dhanya Kellur Nagaraja; Mahendra Kumar Betur Jayappa (Liaquat National Journal of Primary Care, 2026)
A growing body of research demonstrates that the composition of the gut microbiome influences central nervous system function through the gut-brain axis, an essential link in neurophysiological processes. Lactobacillus plantarum, a widely studied probiotic, exhibits multiple neuroprotective mechanisms that support its potential as a psychobiotic. This review synthesizes current preclinical and clinical evidence regarding the effects of L. plantarum on cognitive function, neuroinflammation, oxidative stress, and neuronal integrity. Mechanistically, L. plantarum modulates gut microbiota composition and metabolic activity, enhances intestinal barrier integrity, and attenuates systemic inflammation, thereby reducing neuroinflammatory cascades. Its metabolites, including short-chain fatty acids, neurotransmitters, and other neuroactive compounds, may influence synaptic plasticity, neurogenesis, and behavior through both direct and indirect pathways. Furthermore, evidence from experimental models suggests that L. plantarum may exert protective effects against neurodegeneration associated with Alzheimer’s disease, Parkinson’s disease, and age-related cognitive decline. This review also discusses current translational challenges, including strain specificity, optimal dosing strategies, and the need for well-designed clinical trials to establish therapeutic efficacy. Overall, L. plantarum is a promising candidate for microbiome-based interventions to promote cognitive resilience and support neurological health.